Youth Tobacco Use: A pressing global health and human rights challenge - Meducator, The; Lee, Michael Yo-han; Panchal, Puru (The Meducator, 2019)
Youth smoking is prevalent in Indonesia. 90% of Indonesian children have smoked a cigarette by age 13 and many remain as smokers into adulthood. As a result of this addiction, many households have cigarettes as their second highest expenditure. Smoking is a considerable financial burden on families and the Indonesian health system. Previous international and domestic attempts to reduce Indonesian smoking rates from economic, political, and health systems fronts have not succeeded due to lobbying from tobacco corporations. A stronger stance must be considered—one of childhood development and a right to freedom from addiction. Advocating for physician-patient education, age limits, and childhood education to key stakeholders in the federal government may help leverage strategic foreign policies to internationally address this human rights issue.